(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article reflects the psychophysiological and linguistic foundations of the theoretical study of speech defects, the importance of knowledge of the properties, functions, structure and development of language in special pedagogy, the importance of language as a necessary condition for thinking, and the importance of language in the development of society.